Climate Change: International Law and Global Governance Volume I: Legal Responses and Global Responsibility - Ruppel, Oliver C. (Nomos Verlagsgesellschaft mbH & Co. KG, 2013)
The two-volume publication is one of the first attempts to systematically address both international climate change law and global climate change governance. It deals with international law and the multiple regulatory regimes reflecting fragmentation in the absence of a universal climate change regime. International climate change law, global climate governance and diplomacy are interrelated and extremely complex: The publications explore these areas from a variety of doctrinal, transdisciplinary and thematic perspectives.